Predictors of Fatal Outcome in Newly Diagnosed Tuberculosis/HIV Co-Infection with Chronic Alcoholism (Clinical Case) - Raznatovska, O. M.; Petrenko, V. I.; Shalmin, O. S.; Yasinskyi, R. M.; Fedorets, A. V.; Svitlitsky, A. O.; Svitlytska, O. A.; Noreiko, S. B.; Разнатовська, Олена Миколаївна; Петренко, В. І.; Шальмін, Олександр Самуілович; Ясінський, Роман Миколайович; et al. (My University, 2024)
Our own case of tuberculosis/HIV co-infection’s diagnosis in chronic alcoholism and analysis of the fatal outcome predictors are presented. The patient abused alcohol for a long time in the presented case, he was hospitalised with acute psychosis in a psychoneurological dispensary, where pulmonary tuberculosis and HIV infection were diagnosed for the first time during additional examination. The patient was admitted to the department in serious condition after prolonged alcohol intoxication. The patient’s condition stabilized after detoxification therapy. Antimycobacterial therapy according to the scheme of an individual treatment regimen, antiretroviral therapy, treatment of hepatitis B and C, detoxification therapy, prophylaxis with Biseptol and Fluconazole and symptomatic therapy were prescribed. After 20 days immune reconstitution inflammatory syndrome developed. It was manifested with meningitis and cryptococci were detected in the cerebrospinal fluid 17 days later. Prescribed treatment of cryptococcal meningoencephalitis with fluconazole in high doses intravenously had a significant positive effect, which made it possible to reduce the dose of the drug to the maintenance level. The treatment was not stopped, but sterility of the liquor was not achieved. After 98 days the patient entered a coma and after 113 days he died from the progression of multiple organ failure and cryptococcal meningitis. It should be noted that the patient was diagnosed with tuberculosis with multiple drug resistance for the first time, the treatment of which had positive dynamics, despite the progression of multiple organ failure and the presence of cryptococcal meningoencephalitis. Therefore, although tuberculosis was not the direct cause of the patient’s death, the disease itself deepened the severity of the general condition. Considering the presented clinical case, it was established that predictors of the fatal outcome of newly diagnosed tuberculosis/HIV co-infection in chronic alcoholism are: antisocial lifestyle; concomitant diseases (tuberculosis, chronic viral hepatitis B and C); cryptococcal meningoencephalitis; fever, altered mental status, cryptococci in the cerebrospinal fluid; the number of CD4+ lymphocytes is less than 200/μL; lack of early screening for CrAg; early initiation of antiretroviral therapy before the diagnosis of cryptococcal meningoencephalitis, which provokes immune reconstitution inflammatory syndrome, against the background of which cryptococcal infection progresses; monotherapy of cryptococcal meningoencephalitis with Fluconazole. Knowledge and practice gaps among medical practitioners contribute to the high fatality rate of cryptococcal meningoencephalitis in tuberculosis/HIV co-infection in chronic alcoholism. Представлено власне спостереження діагностики конфекції туберкульоз/ВІЛ-інфекція при хронічному алкоголізмі й аналіз предикторів летального наслідку. Пацієнт тривалий час зловживав алкоголем. Потрапив із гострим психозом у психоневрологічний диспансер, де при дообстеженні вперше діагностовано туберкульоз легень і ВІЛ-інфекцію. Пацієнта госпіталізовано у відділення в тяжкому стані після тривалої алкогольної інтоксикації. Після проведення дезінтоксикаційної терапії стан стабілізувався. Призначено антимікобактеріальну терапію за схемою індивідуального режиму лікування, антиретровірусну терапію, лікування гепатитів В і С, дезінтоксикаційну терапію, профілактику бісептолом і флуконазолом, симптоматичну терапію. Через 20 днів розвинувся синдром відновлення імунної системи із виявами менінгіту. Через 17 днів після цього в лікворі виявлено криптококи. Лікування криптококового менінгоенцефаліту флуконазолом у високих дозах внут рішньовенно було ефективним, що дало змогу зменшити дози препарату до підтримувальної. Лікування не припиняли, але санації ліквору не зафіксовано. Через 98 днів пацієнт увійшов у кому, а через 113 днів помер від прогресування поліорганної недостатності та криптококового менінгіту. У пацієнта був вперше виявлений туберкульоз із множинною лікарською стійкістю, лікування якого мало позитивну динаміку, незважаючи на прогресування поліорганної недостатності та наявність криптококового менінгоенцефаліту. Тому туберкульоз хоча і не був безпосередньою причиною смерті пацієнта, але підсилював тяжкість загального стану. З огляду на наведений клінічний випадок установлено, що предикторами летального наслідку вперше діагностованої ко-інфекції туберкульоз/ВІЛ при хронічному алкоголізмі є: асоціальний спосіб життя, супутні захворювання (туберкульоз, хронічний вірусний гепатит В і С), криптококовий менінгоенцефаліт, лихоманка, змінений психічний стан, наявність криптококів у лікворі, кількість CD4-лімфоцитів < 200/мкл, відсутність раннього скринінгу на CrAg, ранній початок антиретровірусної терапії до встановлення діагнозу криптококового менінгоенцефаліту, що провокує появу синдрому відновлення імунної системи, на тлі якого відбувається прогресування криптококової інфекції, монотерапія криптококового менінгоенцефаліту флуконазолом. Висока частота ле тальних наслідків від криптококового менінгоенцефаліту при ко-інфекції туберкульоз/ВІЛ-ін фек ція на тлі хронічного алкоголізму зумовлена недостатньою обізнаністю практикуючих лікарів.
Предиктори летального наслідку вперше діагностованої ко-інфекції туберкульоз/ВІЛ при хронічному алкоголізмі (клінічний випадок)
Keywords: mortality; tuberculosis; HIV; chronic alcoholism; летальність; туберкульоз; ВІЛ; хронічний алкоголізм